2007
DOI: 10.1212/01.wnl.0000275234.43506.9b
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of inflammation in CNS disease

Abstract: Inflammatory responses in the CNS have usually been perceived to cause or contribute to neuron injury. However, emerging evidence suggests that inflammatory reactions can also be neuroprotective. The nervous and immune systems employ overlapping mechanisms and shared mediators that promote cross-talk between the two systems. Immune cells, for example, produce not only neurodestructive molecules but also factors that can support neuroaxonal growth, survival, and plasticity. This might explain why inflammatory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 45 publications
(56 reference statements)
2
68
0
1
Order By: Relevance
“…Given the intimate and complex relationship between inflammation and remyelination (Hohlfeld et al, 2007;Rodriguez, 2007;Sharief, 1998), it has been suggested that modulation of the local inflammatory milieu might prove to be the most promising therapeutic approach to support remyelination in MS lesions (Franklin and Ffrench-Constant, 2008). Nonetheless, any enterprise to devise therapeutic interventions that would aim at establishing or ameliorating the remyelination-supportive cellular environment in the CNS of patients with MS has been greatly hindered by the lack of knowledge regarding the exact nature of this cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Given the intimate and complex relationship between inflammation and remyelination (Hohlfeld et al, 2007;Rodriguez, 2007;Sharief, 1998), it has been suggested that modulation of the local inflammatory milieu might prove to be the most promising therapeutic approach to support remyelination in MS lesions (Franklin and Ffrench-Constant, 2008). Nonetheless, any enterprise to devise therapeutic interventions that would aim at establishing or ameliorating the remyelination-supportive cellular environment in the CNS of patients with MS has been greatly hindered by the lack of knowledge regarding the exact nature of this cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…This dual role of TNF-α may underlie the poor outcome observed with inhibition of TNF-α signaling in MS clinical trials [31,32]. TNF signaling is an example of the difficulty of predicting effects of growth factors and cytokines associated with inflammation, which can positively and negatively impact remyelination [33,34]. A further example is that induction of localized inflammation promoted remyelination of transplanted cells in the context of chronic demyelination [35].…”
Section: Stimulating Proliferation To Counter Op Depletion In Chronicmentioning
confidence: 99%
“…Recent literature data show the presence of intense cross-talk between the nervous and the immune system [13,18,30]. The elements of both systems express and secrete a range of cytokines (for the immune system) and neurotrophic factors (for the CNS) that control growth as well as cell differentiation.…”
Section: Resultsmentioning
confidence: 99%